2011
DOI: 10.1021/la2005612
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Controlled Metal Binding on Polyelectrolyte-Functionalized Nanopores

Abstract: Most of the research in the field of nanopore-based platforms is focused on monitoring ion currents and forces as individual molecules translocate through the nanopore. Molecular gating, however, can occur when target analytes interact with receptors appended to the nanopore surface. Here we show that a solid state nanopore functionalized with polyelectrolytes can reversibly bind metal ions, resulting in a reversible, real-time signal that is concentration dependent. Functionalization of the sensor is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…13 By using chemical receptors, solid-state nanopores have been engineered to respond to stimuli such as nucleic acids, 14 proteins, 15 small molecules, 16 and metal ions. 17, 18, 19, 20 As with binding of metal ions, the most sensitive and reversible systems are those in which the stimulus modulates surface charge within the nanopores. This is true for pH-responsive nanopores, prepared by attaching acidic or basic moieties onto pore walls and causing current rectification to be modulated with protonation state.…”
Section: Introductionmentioning
confidence: 99%
“…13 By using chemical receptors, solid-state nanopores have been engineered to respond to stimuli such as nucleic acids, 14 proteins, 15 small molecules, 16 and metal ions. 17, 18, 19, 20 As with binding of metal ions, the most sensitive and reversible systems are those in which the stimulus modulates surface charge within the nanopores. This is true for pH-responsive nanopores, prepared by attaching acidic or basic moieties onto pore walls and causing current rectification to be modulated with protonation state.…”
Section: Introductionmentioning
confidence: 99%
“…18, 19 Nanopipette have been recently utilized to measure the electrophysiology at small synaptic boutons, 20 to locally deliver molecules to multiple subcellular areas, 21 and to trap molecules in lipid bilayers. 22 Our group has developed nanopipettes as a label-free sensing platform 23–28 and we recently described an adaptation of SICM allowing the multi-component injection of single cells in culture. 29 Laforge et al .…”
mentioning
confidence: 99%
“…Baker et al 22 have suggested that ICR could be enhanced or reduced through the electrostatic interactions between a neutral or a charged nanopipette and a charged substrate. In addition, many others have modified the surface of pipettes to explore the ICR phenomenon with different types of polymers, such as polylysine, 23 poly(acrylic acid), 24 chitosan, 25 and polymine. 26 Currently, almost all of the studies about ICR have been carried out in aqueous solutions, and mostly using KCl as the electrolyte; 26 only a few solvents other than water have been involved.…”
mentioning
confidence: 99%